Influence of acidified drinking water on growth performance and gastrointestinal function of broilers. (1st June 2018) - Hamid, H; Shi, H Q; Ma, G Y; Fan, Y; Li, W X; Zhao, L H; Zhang, J Y; Ji, C; Ma, Q G
Abstract: The ban on the use of antibiotic feed additives as growth promoters compelled the researchers for exploring the future utility of other alternatives. This experiment was designed to evaluate the effect of acidified drinking water on growth performance, gastrointestinal pH, digestive enzymes, intestinal histomorphology, and cecum microbial counting of the broiler chicken. A total of 540 one-day-old male broilers (Arbor Acre) were randomly assigned to 5 treatments, with 6 replicates of 18 chicks per replicate. Broilers received diets and water as follows: NC (negative control, basal diet, normal water), PC (positive control, basal diet + 8 ppm colistin sulfate + 8 ppm enduracidin, normal water), A1 (basal diet, continuous supply of acidified water during whole experiment period), A2 (basal diet, intermittent acidification of water during 0 to 14 d, 22 to 28 d, and 36 to 42 d), and A3 [basal diet, intermittent acidification of water (24 h/d from 0 to 14 d and from 10:00 am to 4:00 pm on d 15 to 42)]. During the entire period, the acidified groups (A1, A2, and A3) and PC group showed improve on weight gain, average daily gain and feed conversion ratio compared to NC group ( P < 0.05). The pH in crop, proventriculus and ileum at 43 d declined by 0.04, 1.03, 1.23; 0.55, 0.69, 0.70; and 0.63, 0.74, 1.21 in A1, A2, and A3 group, respectively. There was a significant decline of lipase activity in the PC and acidified groups compared to NC group. The A2 group had higher villus height in jejunum than NC group. The PC and acidified groups reduced ( P < 0.05) the total aerobic bacteria count of cecum when contrasted to NC group. Therefore, we conclude that acidified drinking water can improve growth performance, compensate for gastric acidity, and control pathogenic bacteria in broilers and may be considered as a potential alternative to improve production parameters. Discontinuous supply of acidified water had the same or even better influence on broilers compared to continuous supply.